Housing Conditions in Rural Nigeria: Empirical Evidence from Oil-Rich Akwa Ibom State - Usen Udoh (Iranian Journal of Health, Safety and Environment, 2016)
The study assessed the conditions of rural housing and the extent to which housing conditions related to household socio-economic characteristics of an oil-rich Nigerian State of Akwa Ibom. The study design was based on household cross-sectional survey. Direct observation and questionnaire administration were employed to collect both socio-economic and housing data from 540 randomly sampled households spread across 90 rural communities. Housing condition was evaluated using five broad indicators: safety/security, indoor temperature/ventilation, building condition, hygiene/sanitation and environmental quality, while socio-economic characteristics were examined using income, educational attainment, occupation, household size and crowding. Alongside descriptive statistics, the multiple correlation technique was used to analyze the relationship between housing conditions and socio-economic variables. Results showed aEnviron overwhelmingly poor condition of housing among the rural households. Majority of households were found deficient in facilities necessary to encourage safety, security, comfort, hygiene, sanitation, and environmental quality. The study also found households' socio-economic characteristics to be highly correlated with housing conditions and therefore provides the basis for massive rural empowerment and development drive as a means to counter rural housing decay.